Virtual reality games for rehabilitation of upper extremities in stroke patients. (April 2021) - Shahmoradi, Leila; Almasi, Sohrab; Ahmadi, Hossein; Bashiri, Azadeh; Azadi, Tania; Mirbagherie, Alireza; Ansari, Noureddin Nakhostin; Honarpishe, Roshanak
Abstract: Introduction: Stroke is one of the main causes of physical disability in which doing frequent and early exercise is imperative for rehabilitation. Virtual reality gaming has a high potential in rehabilitation leading to increased performance of patients. This study aimed to develop, validate and examine virtual reality games in chronic stroke patients. Methods: This was a single before-after study. To determine the movements and content of games, 9 physiotherapists and 11 game designers were asked to participate in a questionnaire-based survey. Then, to evaluate the impact of games on rehabilitation, patients (N = 10; mean age = 52 ± 4.38) with chronic stroke were asked to play the games three times a week for four weeks. Outcomes included measurement of the ability to perform shoulder, elbow and wrist movements was performed using goniometric instrument, Modified Motor Assessment Scale (MMAS) was used to assess the functional ability of patients and muscle spasticity, and brunnstrom's stages of recovery test was also used to assess spastic and involuntary muscle movement. Results: Games have positive effects on the horizontal abduction of shoulder (16.26 ± 23.94, P = 0.02), horizontal adduction of shoulder (59.24 ± 74.76, P = 0.00), supination of wrist (10.68 ± 53.52, P = 0.02), elbow flexion (0.1 ± 1.5, P = 0.00), and wrist flexion (0.06 ± 1.34, P = 0.03). However, they had no effects on the flexion of shoulder, flexion of elbow, extension of elbow, and extension of wrist (p-value> 0.05). Conclusions: The results showed that games improve the range of motion of the participants in terms of horizontal abduction and abduction of the shoulder, elbow flexion, and supination and flexion of the wrist. Due to the small sample size in this study, we recommend more studies with larger samples and a control group.